Effects of Glucagon-Like Peptide-1 Receptor Agonist Exendin-4 on the Reinstatement of Cocaine-Mediated Conditioned Place Preference in Mice - Zhu, Changliang; Wang, Lei; Ding, Jiangwei; Li, Hailiang; Wan, Din; Sun, Yangyang; Guo, Baorui; He, Zhenquan; Ren, Xiaofan; Jiang, Shucai; Gao, Caibing; Guo, Hua; et al. (Frontiers in Behavioral Neuroscience, 2022)
A high percentage of relapse to compulsive cocaine-taking and cocaine-seeking behaviors following abstinence constitutes a major obstacle to the clinical treatment of cocaine addiction. Thus, there is a substantial need to develop effective pharmacotherapies for the prevention of cocaine relapse. The reinstatement paradigm is known as the most commonly used animal model to study relapse in abstinent human addicts. The primary aim of this study is to investigate the potential effects of systemic administration of glucagon-like peptide-1 receptor agonist (GLP-1RA) exendin-4 (Ex4) on the cocaine- and stress-triggered reinstatement of cocaine-induced conditioned place preference (CPP) in male C57BL/6J mice. The biased CPP paradigm was induced by alternating administration of saline and cocaine (20 mg/kg), followed by extinction training and then reinstatement by either a cocaine prime (10 mg/kg) or exposure to swimming on the reinstatement test day. To examine the effects of Ex4 on the reinstatement, Ex4 was systemically administered 1 h after the daily extinction session. Additionally, we also explored the associated molecular basis of the behavioral effects of Ex4. The expression of nuclear factor κβ (NF-κβ) in the nucleus accumbens (NAc) was detected using Western blotting. As a result, all animals that were treated with cocaine during the conditioning period successfully acquired CPP, and their CPP response was extinguished after 8 extinction sessions. Furthermore, the animals that were exposed to cocaine or swimming on the reinstatement day showed a significant reinstatement of CPP. Interestingly, systemic pretreatment with Ex4 was sufficient to attenuate cocaine- and stress-primed reinstatement of cocaine-induced CPP. Additionally, the expression of NF-κβ, which was upregulated by cocaine, was normalized by Ex4 in the cocaine-experienced mice. Altogether, our study reveals the novel effect of Ex4 on the reinstatement of cocaine-induced CPP and suggests that GLP-1R agonists appear to be highly promising drugs in the treatment of cocaine use disorder.